Bulletin 73 Brass Furnace Practice - H. W. Gillett (The National Institute for Occupational Safety and Health (NIOSH), 1914)
This bulletin is issued by the Bureau of Mines as a contribution to the increase of safety and efficiency in the preparation and utilization of the mineral resources in the United States. Notable among the drains on these resources are the demands made by the nonferrous- metal industries, and in these the losses occasioned in melting brass and bronze are worthy of particular attention. This statement will be better appreciated by a consideration of the size of the brass industry.